A heatline analysis of natural convection in a square inclined enclosure filled with a CuO nanofluid under non-uniform wall heating condition - Öztop, Hakan Fehmi; Mobedi, Moghtada; Abu-Nada, Eiyad; Pop, Ioan (Pergamon-Elsevier Science Ltd, 2012)
Heatline visualization technique is used to understand heat transport path in an inclined non-uniformly heated enclosure filled with water based CuO nanofluid. The cavity has square cross-section and it is non-uniformly heated from a wall and cooled from opposite wall while other walls are adiabatic. The governing equations which are continuity, momentum and energy equations are solved using finite volume method. The dimensionless heatfunction for nanofluid heat flow is defined and solved to determine heat-line patterns. Calculations were performed for Rayleigh numbers of 10(3), 10(4) and 10(5), inclination angle of 0 degrees, 30 degrees, 60 degrees and 90 degrees, and nanoparticle fraction of 0, 0.02, 0.04, 0.06, 0.08 and 0.1. It is observed that heat transfer in the cavity increases by adding nanoparticles. The rate of increase is greater for the enclosures with low Rayleigh number. Visualization of heatline is successfully applied to nanoparticle convective flows. Based on the heatline patterns, three heat transfer regions are observed and discussed in details. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Heatline; Nanofluid; Natural convection; Enclosure